Legal Protection of Investors Due to Misleading Information in the Sharia Capital Market Perspective of DSN MUI Fatwa Number 80 of 2011 - Asrul Saputra Harahap; Fauziah Lubis (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of writing this scientific journal is to find out the regulations and legal protection for investors who suffer losses due to misleading information, which is one of the practices of market manipulation in stock trading in the capital market, viewed from the aspect of legal protection for investors from the perspective of DSN MUI fatwa No. 80 of 2011. Misleading information is a form of market manipulation that can harm investors and requires legal protection. Investors and the public need to know more clearly about market manipulation practices found in the capital market, especially in the Sharia capital market. In the capital market, there is fraud in the form of market manipulation, one form of which is the act of providing misleading information. The research method used in this writing is a normative juridical approach. The normative juridical approach is an approach carried out by examining theories, concepts, legal principles, and statutory regulations related to this discussion. The research results show that in most cases that occur in the capital market, the object is information that can influence securities prices and investment decisions for investors. The practice of misleading information is an activity used to create a false picture regarding buying and selling activities and prices on the stock exchange. This activity is usually carried out by individuals in the capital market with the aim of influencing securities prices and disseminating incomplete and misleading information. Legal protection that can be carried out is preventive and repressive protection. Preventive legal protection is carried out by providing education to the public and monitoring transactions carried out by the Financial Services Authority (OJK), while repressive legal protection includes litigation, non-litigation, and sanctions. Suggestions for future research are that researchers can find research results that lead to examples of preventive and repressive protection that have been implemented in Indonesia.